2014
DOI: 10.5704/moj.1403.001
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Tuberculosis of Talus: A Case Report

Abstract: Tuberculosis still remains a leading infection, causing death and disability worldwide. We report a patient with isolated tuberculosis of the talus bone. A 14 year old boy reported with an eight-month history of swelling and pain in his left ankle joint. Routine investigations indicated positive aetiology of tuberculous infection . Surgical curettage of the talus and, debridement were performed and a below knee POP cast was applied along with anti TB therapy. After 18 months postoperative , the patient was abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
1
6
0
1
Order By: Relevance
“…The symptom that often occurs is a pain in the right upper abdomen, weight loss, nausea, vomiting, and diarrhea [9]. Other symptoms, such as jaundice, are rare.…”
Section: Discussionmentioning
confidence: 99%
“…The symptom that often occurs is a pain in the right upper abdomen, weight loss, nausea, vomiting, and diarrhea [9]. Other symptoms, such as jaundice, are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is a very common infection in developing countries like India leading to significant impairment and ultimately death [8] . Plantar region affection by the disease is a relatively rare occasion [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB) infection is a grave problem for the medical society, especially in the third-world healthcare systems. Although it manifests in the pulmonary system, in the majority of cases, non-pulmonary systems including musculoskeletal system can get involved in as much as for 30% of the patients [ 3 ]. The most common sites affected osteoarticularlar TB include the spine, hip, and knee [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of the foot and ankle TB cases, Dhillon, et al found only a single case of talus TB out of 992-foot cases over a period of 20 years [ 5 ]. Dahuja, et al reported a case of isolated TB of the talus treated with surgical curettage and debridement along with anti-TB chemotherapy giving good results [ 3 ]. Halwai, et al reported the use of transmalleolar osteotomy for surgical debridement and obtaining tissue samples in a talar TB case who had a normal ankle joint range of motion after six years [ 10 ].…”
Section: Discussionmentioning
confidence: 99%